Relevansi pemeriksaan medis modern terhadap status iddah dalam hukum keluarga islam - Sya’baniyah, Najwa (Maliki Interdisciplinary Journal, 2025)
Iddah is a waiting period that a wife must observe following a divorce or the death of her husband. Classical Islamic jurisprudence (fiqh) states that one of the purposes of iddah is to ensure the wife’s womb is free of sperm from her previous husband before marrying a new husband. Advances in medical technology, such as ultrasounds, DNA tests, pregnancy tests, and so on, have raised the question of whether the iddah period is still relevant if the certainty of uterine emptiness can be determined quickly and accurately. This study uses a literature review approach to classical Islamic jurisprudence sources and contemporary literature. This study shows that although medical certainty can provide faster information, the issue of iddah is not only a biological issue but also considers the background to the obligation of iddah. Therefore, discussing the role of medical technology in iddah requires a careful approach and continues to consider the values ​​of Islamic law as a whole.